Assessing Hygenic Practices, Sanitation Procedures of Housekeeping Department Perceived by Hotels-Motels Housekeeping Heads - Mangco, Charisma Amor; Andales, Norman (International Journal Labs, 2023)
Background: A clean, comfortable, and safe environment for guests, visitors, and employees is the primary responsibility of a hotel's housekeeping department. A good operation in this area may be the best public relations a hotel can have. Aim: This study aims to assess the Housekeeping department's hygienic practices and sanitation procedures as perceived by Housekeeping Heads of selected hotels and motels in Biliran Province, Philippines. Method: A descriptive-survey research design was employed in this study. The research respondents comprised the Housekeeping Heads of selected hotels and motels in Biliran Province, Philippines. The assessment instrument used was a five-point Likert Scale questionnaire. Findings: The results of the study revealed that the Housekeeping Heads of selected hotels and motels in Biliran Province, Philippines generally perceived their department’s hygienic practices and sanitation procedures to be satisfactory. Furthermore, a significant difference was found in the perception of the Housekeeping Heads of the hotels and motels in the area regarding the implementation of the hygienic practices and sanitation procedures of their department